2020
DOI: 10.1021/acs.chemrev.9b00439
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen K-edge X-ray Absorption Spectra

Abstract: We review oxygen K-edge X-ray absorption spectra of both molecules and solids. We start with an overview of the main experimental aspects of oxygen K-edge X-ray absorption measurements including X-ray sources, monochromators, and detection schemes. Many recent oxygen K-edge studies combine X-ray absorption with time and spatially resolved measurements and/or operando conditions. The main theoretical and conceptual approximations for the simulation of oxygen K-edges are discussed in the Theory section. We subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
328
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 438 publications
(357 citation statements)
references
References 481 publications
25
328
0
4
Order By: Relevance
“…The features B 1 (at 533.4 eV) and B 2 (at around 540.0 and 544.0 eV) can be assigned to the CO 1s–π* transition and the CO and CO 1s–σ* transition in Li 2 CO 3 . [ 50,51 ] Furthermore, all spectra also show a shoulder of peak A at around 532.2 eV, which is related to ROCO 2 Li alkyl carbonates. [ 25 ] Note that the latter signal also overlaps with a peak of Li 2 O.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The features B 1 (at 533.4 eV) and B 2 (at around 540.0 and 544.0 eV) can be assigned to the CO 1s–π* transition and the CO and CO 1s–σ* transition in Li 2 CO 3 . [ 50,51 ] Furthermore, all spectra also show a shoulder of peak A at around 532.2 eV, which is related to ROCO 2 Li alkyl carbonates. [ 25 ] Note that the latter signal also overlaps with a peak of Li 2 O.…”
Section: Resultsmentioning
confidence: 99%
“…[ 25 ] Note that the latter signal also overlaps with a peak of Li 2 O. [ 51,52 ] For ZnO, the shoulder peak A is most intense upon lithiation, for example, at 0.4 V and, thus, after the conversion reaction (Figure 6e). This increase in intensity of feature A is ascribed to the formation of larger Li 2 O aggregates during the conversion reaction, since pure ZnO lacks the “confinement effect” by the transition metal nano‐network.…”
Section: Resultsmentioning
confidence: 99%
“… 117 At the same time, information from the K-edges of light elements can provide important complementary insight about the structure of multielement catalysts, 114 or that of the electrolyte, 84 interactions between adsorbates and catalysts, 118 , 119 and structural motifs in carbon-based materials that are currently used as nonprecious metal catalysts for the CO 2 electroreduction and oxygen reduction reactions. 120 123 An excellent review on the measurements and interpretation of O K-edge XAS was recently published by Frati et al 83 …”
Section: Xas Experimentsmentioning
confidence: 99%
“… 573 An alternative interpretation was, however, proposed by Frati et al., who suggested that the observed changes in the O K-edge XANES can be rather attributed to the formation of Ir 5+ species in the presence of Ir vacancies. 83 …”
Section: Examplesmentioning
confidence: 99%
“…The TD-DFT calculations were split into three groups; a convolution of the theoretical data was performed for each group with one third of the data, using Lorentzian functions with a width of half maximum of 0.20 eV, which is in the range of observed values for the core-hole K-edge lifetime broadening of oxygen. 16,17 The theoretical spectra shown in our figures represent the average for the spectra of the three groups. The shadows around each curve represent the standard deviation of the three groups, which can be interpreted as an error measure.…”
Section: Details About the Convolution Of The Theoretical Spectramentioning
confidence: 99%